Benzylated phenanthrenes from Eulophi nuda - Patoomratana Tuchinda (2018)
From the tubers of Eulophia nuda, further phenanthrene derivatives have been isolated: 9, 10-dihydro-1-(4′-hydroxybenzyl)-4,7-dimethoxyphenanthrene-2,8-diol, 1-(4′-hydroxybenzyl)-4,8-dimethoxyphenanthrene-2-7-diol. In addition, 3,4′-dihydroxy-3′,5,5′-trimethoxybibenzyl and bis(4-hydroxybenzyl) ether were obtained. The structures were assigned by spectroscopic methods. The structure of the penultimate compound mentioned above was also confirmed by synthesis. © 1989.